ANALYSIS OF TIME-ZONE RELATIONSHIP TO EPHEMERIS DATA RETRIEVAL IN CALCULATING THE BEGINNING OF JEMBRANA-BANYUWANGI PRAYER TIMES - Setya, Agus; Azkarrula, Youla Afifah (Al-Hilal: Journal of Islamic Astronomy, 2024)
The calculation of prayer times in Bali and Banyuwangi Regency often needs to be clarified. Hasib suggests Bali's prayer time calculations could refer to those in Banyuwangi due to their close astronomical coordinates. While Bali uses the Central Indonesian Time Zone (WITA, GMT+8), Banyuwangi adopts the Western Indonesian Time Zone (WIB, GMT+7). This discrepancy arises despite the proximity of their locations, reflecting government decisions based on international considerations, especially after Bali was reassigned from WIB to WITA through Presidential Decree No. 41 of 1987. This library research uses qualitative methods such as documentation and descriptive analysis. It shows that the differences in prayer time calculations between Bali and Banyuwangi are minimal, often just a matter of seconds, mainly if there is an error in inputting Ephemeris data. However, such errors have no significant impact as long as the date remains consistent and time zone corrections adhere to official regulations.